Fuzzy Algorithms for Selection of Bidding Strategies - Ilieva, Galina (Cybernetics and information technologies : CIT, 2010)
The subject of the work is investigating algorithms for multicriteria decision making with fuzzy logic. The aim of the work is proving that algorithms with fuzzy criteria can successfully be used for solving the task of multicriteria ordering of bidding strategies in an auction. Two algorithms have been compared: one with aggregation operators (ATOKRI) and one with attitude alternative-criterion (FTNA). The major similarity between the two algorithms is that they both use fuzzy relations as a tool for choosing the optimal alternative. The key difference between them is in the subjectivism rate and the influence of the decision maker's attitude towards the compared alternatives and criteria. Despite the differences in the obtained strategy orders, both algorithms give results that are close to those of the 'classical' algorithms for multicriteria analysis. Therefore, the two algorithms offer efficient ways for finding a solution of the task of multicriteria selection of bidding strategy in an auction under incomplete and uncertain information and changing conditions.